PERSPEKTIF VALUE FOR MONEY DALAM PENGUKURAN KINERJA PERANGKAT DAERAH - Tama, Annafi Indra (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2017)
The purpose of this research is to know the performance of West Java Provincial Food Security Agency with value for money approach (VFM), that is 3E measurement (economical, efficiency, and effectiveness). The results of the research show that the economic level during 2013, 2014 and 2015 has increased by 102.27%, but the increase that makes the ratio does not meet the economic standard value for money. Efficiency levels during 2013, 2014 and 2015 continue to increase in economic value, the ratio is below 100% so that for efficiency ratios do not meet the standard efesien value for money. Effectiveness ratios during 2013, 2014 and 2015 with a> 100% assessment indicating that the Regional Food Security Agency of West Java Province has been effective in providing services to the community. Effectiveness ratio in 2013 and 2014 has effectiveness value> 100% but in 2015 decreased to 97,48% but still effective categorized, but still needed existence of improvement of service so that effectiveness of West Java Provincial Food Security Agency achieved better.